Performance of Mberekan Pedah-pedah Mengket Rumah Mbaru in Karonese Tradition - Alemina Br. Perangin-Angin (IPMI Publisher, 2019)
Mengket rumah mbaru is a joyous event to enter a new home, this event involves kalimbubu, anak beru, and senina. In the implementation of the event. These three groups are the core participants to carry out the events. They also have they own roles and responsibilities to give advises, pray, and wishes to homeowner. This study uses an anthropolinguistics approach to describe the performance of mbereken pedah-pedah. This research is a qualitative descriptive study, involving researchers directly in the implementation of the event, to get data in the field conducted in-depth interviews with informants who are still carrying out the event. Mbereken pedah-pedah is a form of mutual cooperation as well as a form of kinship among the Karonese people which is still strong.